2010
DOI: 10.1037/a0019646
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-based priming of task choice during voluntary task switching.

Abstract: Two voluntary task-switching experiments probed the influence of previous exposures to stimuli and categorizations of these stimuli on task choice during subsequent exposures to the same stimuli. Subjects performed origin and size judgments under standard voluntary task-switching instructions to perform the tasks equally often in a random order. Both when subjects voluntarily selected the task on the first exposure (Experiment 1) and when the experimenter manipulated the task on the first exposure (Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…Therefore, its subsequent reappearance may have primed participants to repeat that response (Hommel, 1998), and this bias might somehow have been greater following incongruent and/or incorrect trials. This possibility is consistent with previous findings suggesting an influence of stimulus-response priming on voluntary task choice (Arrington, Weaver, & Pauker, 2010;Demanet, Liefooghe, Verbruggen, & Vandierendonck, 2010;Mayr & Bell, 2006).…”
Section: Methodssupporting
confidence: 88%
“…Therefore, its subsequent reappearance may have primed participants to repeat that response (Hommel, 1998), and this bias might somehow have been greater following incongruent and/or incorrect trials. This possibility is consistent with previous findings suggesting an influence of stimulus-response priming on voluntary task choice (Arrington, Weaver, & Pauker, 2010;Demanet, Liefooghe, Verbruggen, & Vandierendonck, 2010;Mayr & Bell, 2006).…”
Section: Methodssupporting
confidence: 88%
“…Task difficulty may have been induced by the order in which tasks were practiced; the parity task was the first task participants practiced. The initial task performed by a participant during the experimental session has been shown to bias later task choices (Arrington, Weaver, & Pauker 2010). The correlation of p(parity) with WMC suggests that this bias was more pronounced for individuals with lower WMC.…”
Section: Discussionmentioning
confidence: 96%
“…These predictions were generated from the view that task choice processes include maintaining a representation of the most recent sequence of tasks, updating that representation as new tasks are performed, and making a choice about what constitutes a random sequence while resisting the biasing influence of the previously executed task (Arrington & Logan, 2005;Mayr & Bell, 2006) and while ignoring environmental information to guide task choice (Arrington, 2008;Arrington & Logan, 2005;Arrington et al, 2010;Demanet et al, 2010). Goal maintenance and updating while resisting the biasing influence of competing sources of information seem to be precisely the conditions that reveal WMC-related differences in other tasks (see , for a review).…”
Section: Task Choicementioning
confidence: 99%
“…Intuitively one would think that free choices are mostly determined by our own intentions and internal goals. Previous research, however, suggests that free choices may not be as free as they seem to be, and are strongly influenced by cues from the environment or past experiences (Bargh et al, 2001;Arrington & Logan, 2005;Arrington, Weaver & Pauker, 2010;Wenke, Fleming & Haggard, 2010;Orr & Weissman, 2011;Orr, Carp, & Weissman, 2012;Demanet et al, 2013;Orr & Banich, 2014). Wenke and colleagues (2010), for example, found that subliminal primes influence the responses on free choice trials in such a way that people responded significantly more slowly when they chose to act against the prime (in a prime-incompatible way).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%